Synthesis of 1,4-diazabicyclo[2.2.2]octane and pyridinium based cationic polymers via ROMP technique and examination of their antibacterial activity and cytotoxicity - SEZER, ALİ DEMİR; AKSU, MEHMET BURAK (ELSEVIER SCI LTD, 2019)
This paper focuses on the synthesis of cationic antibacterial polymers that could be a potential source for new-generation antibiotics with well-defined architecture derived from the Ring Opening Metathesis Polymerization (ROMP) technique. Mono- and double-charge bearing quaternary groups have been used to synthesize cationic homopolymers (MWs: 3000 and 10,000 g/mole) and their copolymers (MWs: 5000 g/mole). Hemolytic concentration (HC50, >= 1000 mu g/mL) and MTS assay results showed that the polymers are non-toxic. It has been observed that the double-charge bearing polymers have the highest antimicrobial activity (S. aureus= 8 mu g/mL) and a high selectivity against S. aureus (>250). Percent killing efficiencies were tested on a glass surface where moderate killing efficiency was observed in the range of 40-80% in 5 min. Cationic charge density and zeta potential studies were used to investigate the mechanisms of antimicrobial efficiency of the polymers in a solution during the action against S. aureus to understand structure-activity relationships. Scanning electron microscopy (SEM) was also conducted for the bacterial morphology assay.
Keywords: ROMP; DABCO; Pyridinium; Hemolytic concentration; Antimicrobial activity; Cationic polymer; OPENING METATHESIS POLYMERIZATION; ANTIMICROBIAL POLYMERS; CHARGE-DENSITY; SURFACE; MIMICS